The Elpsa Framework for The Students’ Spatial Reasoning Ability in Aceh - Nanda Rahmatul Wahidah; Rahmah Johar; Cut Morina Zubainur (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
Geometry is one of the topics that students must comprehend in mathematics. However, in reality, the students' ability concerning geometry is relatively low due to their low spatial reasoning ability. The ELPSA framework is one of the solutions to develop students' spatial reasoning abilities. This study aimed to describe students' spatial reasoning ability and the impact on retention through the ELPSA framework. This research was part of the ELPSA framework research and development. The subjects were four students, chosen from 25 Grade 7 students from one of the junior high schools in Banda Aceh. They were selected based on the percentage of spatial reasoning aspects mastered. The instrument used was a semi-structured interview that was preceded by a written test. The results showed that the four subjects could manipulate objects in their mind to change the shape of D-3 to D-2. However, one of them could not determine its relation precisely. Three out of four subjects could imagine the appearance of an object from different perspectives. Besides, two out of four subjects could visualize objects to determine the number of unit cubes contained in the solid geometry and only one subject could imagine objects from various perspectives to determine the surface area but did not use the given measurement.